Regioselective N-alkylation of some 2-(Substituted Phenyl) Imidazo[4,5-c] Pyridines: Synthesis and Structure Elucidation by NMR" - Göker, Hakan; Özden, Seckin (International Journal of Psychosocial Rehabilitation, 2019)
Imidazopyridines can exist in a few tautomeric systems, as an instance, benzimidazole or purine consolidated frameworks. Regioselectivities have been resolved for N-alkylations of some 2-(substituted phenyl) imidazo [4,5-c] pyridines with benzyl bromides under important situations (K2CO3 in DMF). It became visible that N-five regioisomers were essentially framed. Their number one assignments were carried out -dimensional 1H-1H NOE (atomic over hauser effect spectroscopy [NOESY]) upgrades the various N-CH2 and protons on the C-4H and C-6H locations of the pyridine moiety. To check the NOESY facts, amalgamation of mixes 4b modified into done by using way of the unique approach. Correlative auxiliary data changed into given via second-HMBC spectra of the mixes.